256 Heat stress and β-adrenergic agonists alter the adipose transcriptome and fatty acid mobilization in ruminant livestock. (30th November 2020) - Reith, Rachel R; Sieck, Renae L; Grijalva, Pablo C; Duffy, Erin M; Swanson, Rebecca M; Fuller, Anna M; Beede, Kristin A; Beard, Joslyn K; Diaz, Duarte E; Schmidt, Ty B; Yates, Dustin T; Petersen, Jessica L
Abstract: Heat stress (HS) negatively impacts livestock performance and carcass traits while beta-adrenergic agonist (βAA) supplementation improves animal production and efficiency; both can stimulate lipolysis in adipose. The objective of this study was to understand the independent and interacting effects of HS and βAA on the subcutaneous adipose transcriptome in lambs and on visceral adipose fatty acid mobilization in steers. For study 1, 24 wethers were assigned to thermal neutral (TN THI = 65) or HS (THI = 80) conditions and supplemented without (NS) or with ractopamine hydrochloride (RH) for 30d in a 2 x 2 factorial. TN lambs were pair-fed the average intake of HS. RNA collected from subcutaneous fat at harvest was sequenced. Differential expression (DE) analyses identified 71 (Padj < 0.05) loci altered due to the interaction of environment and supplement. No DE genes were observed for the main effect of supplement, but HS reduced expression (P < 0.05) of RBM3 and increased expression (P < 0.05) of ATXN7L1. HS was predicted by pathway analyses to impair adipogenesis and fatty acid mobilization. In study 2, 24 steers were assigned to TN (THI = 65) or HS (THI = 83) and NS or zilpaterol hydrochloride (ZH) treatments for 21d in a 2 x 2 factorial. TN steers were pair-fed the intake of their HS cohort. Ex vivo fatty acid mobilization from visceral adipose in response to 0 or 1µM epinephrine was quantified at harvest. Fatty acid mobilization did not differ among groups when unstimulated, but epinephrine-stimulated mobilization was less (P = 0.05) in HS and greater (P < 0.01) in ZH steers. These findings indicate that heat stress-induced reduction of fatty acid mobilization from adipose may be associated with increased expression of stress-responsive genes. Moreover, the stimulatory effect of ZH on epinephrine-induced fatty acid mobilization was present after chronic treatment. Our data have yet to identify an interaction between HS and βAA supplementation that demonstrably impacts well-being.